The Impact of US Nurses’ Personal Religious and Spiritual Beliefs on Their Mental Well-Being and Burnout: A Path Analysis - Harris, Stephanie L. (Journal of religion and health, 2022)
This study addresses the gap in the literature regarding the impact of nurses’ personal religious and spiritual beliefs on their mental well-being and burnout. A model of the association between these factors was tested based on surveys of 207 nurses located in southeastern USA and analyzed to determine the association between religion/spirituality, mental well-being, and burnout. A path analysis supported a model in which, through its positive impact on mental well-being, religion/spirituality was negatively associated with emotional exhaustion and depersonalization and positively associated with personal accomplishment.